THE EFFECT OF USING PEER TUTORIAL METHOD IN TEACHING SPEAKING OF SMP NEGERI 2 ANGKOLA TIMUR - Abdul Rahman Siagian (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The researcher conducted this research at the Grade VIII Students of SMP Negeri 2Angkola Timur. The aims of this research was to find out is there a significant effect of using peer tutorial method in speaking ability of SMP Negeri 2 Angkola Timur. In achieving the purposes of this research, the writer carried out in quantitative approach by applying experimental method. The population of this research was 80 students and the writer uses total sampling technique to get of students. The speaking ability was applied as the instrument of this research; the writer used “t” test formula.Based on the data that has been analyzed, it can be found that (1) the students’ achievement of speaking was “very good” (80,5), (2) there is a significant effect of using peer tutorial method in speaking ability of SMP Negeri 2 Angkola Timur